Awareness, acceptance, and consumption pattern of millets among ever-married women in an urban area of Delhi: A cross-sectional observational study - Arora, Priya; Singh, Vikram (Indian Journal of Community Health, 2024)
Background: Millets are a great source of fiber, minerals, and vitamins and are well-known for their excellent nutritional value. They have been part of traditional diets in India. Aims & Objectives: The study was conducted to assess millet awareness, acceptance, and consumption among married women in an urban area of Delhi. Methodology: A community-based cross-sectional study was conducted using a semi-structured questionnaire to collect information on a sample of 262 married women residing in the Tilak Nagar urban area of Delhi. Results: It was found that 78.9% of middle-class women consume millets at least once a month, compared to 64.9% of lower-class women (P value 0.044, ?2 =4.053). 70.9% of the women who were aware of millet significantly consumed it. Conclusion: The findings showed that consuming millet is strongly linked to both socioeconomic status and awareness about millet.